Frequency control during transients in offshore wind parks using battery energy storage systems. Issue 2 (3rd May 2016) - Falcão, João; Castro, Rui; Ferreira de Jesus, J. M.
ABSTRACT: The main objective of this paper is to study the implementation of a battery energy storage system (BESS) in order to improve the dynamic behaviour of an offshore wind farm. Special attention is given to the frequency excursions limitation in the sequence of a fault on the onshore grid. This goal is accomplished by setting up a case study in which an offshore wind farm is connected to an onshore grid through a high voltage direct current line commutated converter (HVDC-LCC) link. The Power System Simulator for Engineering (PSS/E) simulation tool is used to implement the whole system, including the onshore and offshore grids and the load flow and dynamic models of the conventional generators, the wind turbine generators (WTGs), the HVDC-LCC link and the BESS. With the BESS out of service, some protective actions of the DC link lead to the uncontrolled frequency increase of the WTG, which are consequently tripped out. The BESS proves to be essential, as it allows the offshore wind farm to keep running by maintaining the frequency of the WTG at acceptable levels and therefore bringing the entire system to a steady state operating point.